2023
DOI: 10.1038/s41467-023-38593-4
|View full text |Cite
|
Sign up to set email alerts
|

Cultured meat platform developed through the structuring of edible microcarrier-derived microtissues with oleogel-based fat substitute

Abstract: With the increasing global demand for meat, cultured meat technologies are emerging, offering more sustainable solutions that aim to evade a future shortage of meat. Here, we demonstrate a cultured meat platform composed of edible microcarriers and an oleogel-based fat substitute. Scalable expansion of bovine mesenchymal stem cells on edible chitosan-collagen microcarriers is optimized to generate cellularized microtissues. In parallel, an oleogel system incorporated with plant protein is developed as a fat su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…This production method is known to have a texture more similar to real meat than the method described above ( Ravishankar et al, 2019 ). Yen et al (2023) and others reported that cultured meat produced with MC made of 2% chitosan and 0.2%–0.3% collagen showed low hardness, elasticity, and cohesion in the raw state but that these factors could be improved in the cooked state. Therefore, cultured meat should be produced by manufacturing scaffolds using appropriate concentrations and processing methods to improve appearance, flavor, and texture ( Fig.…”
Section: Textural Characteristics Of Cultured Meatmentioning
confidence: 99%
“…This production method is known to have a texture more similar to real meat than the method described above ( Ravishankar et al, 2019 ). Yen et al (2023) and others reported that cultured meat produced with MC made of 2% chitosan and 0.2%–0.3% collagen showed low hardness, elasticity, and cohesion in the raw state but that these factors could be improved in the cooked state. Therefore, cultured meat should be produced by manufacturing scaffolds using appropriate concentrations and processing methods to improve appearance, flavor, and texture ( Fig.…”
Section: Textural Characteristics Of Cultured Meatmentioning
confidence: 99%
“…Additionally, Ong et al (2021) harnessed the color-changing properties of jackfruit-based scaffolds for porcine myoblasts to imitate the characteristic meat browning of conventional meat while cooking. On the other hand, Yen et al (2023) mimicked meat marbling using fat replacers derived from plant-based oleogels, an example of post-production processing for cultivated meat.…”
Section: Novel Foods and Their Colorsmentioning
confidence: 99%
“…Overall, most of the colorants are natural pigments dominated by the use of beets or paprika. Other techniques used to induce coloration include the addition of plant-based replacers, heme proteins (Hb and Mb), decompartmentalization, Haematococcus pluvialis , ohmic cooking, and color-enhancing additives, such as xylose, laccase, pectin, and lactoferrin ( Bakhsh et al, 2022 ; Huang et al, 2024 ; Jung et al, 2022 ; Liu et al, 2023 ; Ong et al, 2021 ; Sakai et al., 2022 ; Simsa et al, 2019 ; Wen et al, 2022 ; Xia et al, 2022 ; Yen et al, 2023 ). Although the usual color of focus for meat analogues is meat-like red, the cooked coloration was also given importance.…”
Section: Potential Colorants For Novel Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using optimized and scalable methods, cellularized microtissues, oleogel-based fat substitute and transglutaminase crosslinking enabled the formation of these cell-based meat products. The advantage of using transglutaminase is its ability to bind microtissues through enzymatic crosslinking, thus stabilizing and improving the mouthfeel of the meat structures (Yen et al, 2023). The use of transglutaminase in cell-based meat production has been previously reported (Kang et al, 2021;Liu et al, 2022) and no doubt will continue as it improves cell-based meat cohesion, and organoleptic properties (Yen et al, 2023).…”
Section: Edible Mcsmentioning
confidence: 99%